Silicon and Salinity: Crosstalk in Crop-Mediated Stress Tolerance Mechanisms - Khan, Adil; Khan, Abdul Latif; Muneer, Sowbiya; Kim, Yoon-Ha; Al-Rawahi, Ahmed; Al-Harrasi, Ahmed (Frontiers in Plant Science, 2019)
Salinity stress hinders the growth potential and productivity of crop plants by influencing photosynthesis, disturbing the osmotic and ionic concentrations, producing excessive oxidants and radicals, regulating endogenous phytohormonal functions, counteracting essential metabolic pathways, and manipulating the patterns of gene expression. In response, plants adopt counter mechanistic cascades of physio-biochemical and molecular signaling to overcome salinity stress; however, continued exposure can overwhelm the defense system, resulting in cell death and the collapse of essential apparatuses. Improving plant vigor and defense responses can thus increase plant stress tolerance and productivity. Alternatively, the quasi-essential element silicon (Si) – the second-most abundant element in the Earth’s crust – is utilized by plants and applied exogenously to combat salinity stress and improve plant growth by enhancing physiological, metabolomic, and molecular responses. In the present review, we elucidate the potential role of Si in ameliorating salinity stress in crops and the possible mechanisms underlying Si-associated stress tolerance in plants. This review also underlines the need for future research to evaluate the role of Si in salinity stress in plants and the identification of gaps in the understanding of this process as a whole at a broader field level.